Direct Measurement of Electronic Band Structure in Single Quantum Dots of Metal Chalcogenide Composites. Issue 51 (7th October 2018) - Benetti, Daniele; Cui, Daling; Zhao, Haiguang; Rosei, Federico; Vomiero, Alberto
Abstract: Metal chalcogenide quantum dots (QDs) are among the most promising materials as light harvesters in all‐inorganic systems for applications in solar cells and production of solar fuels. The electronic band structure of composite QDs formed by lead and cadmium chalcogenides directly grafted on highly oriented pyrolytic graphite surfaces through successive ionic layer absorption and reaction is investigated. Atomic force microscopy and Kelvin probe force microscopy (KPFM) are applied to investigate PbS, CdS, and PbS/CdS QD systems. The variation of the surface potential of individual QDs is measured, investigating the evolution of the electronic band structure as a function of QD size and composition. A shift of the Fermi level toward more negative values occurs when QD size is increased. The shift is more pronounced in CdS than in PbS, while the composite PbS/CdS exhibits an intermediate behavior. The calculated shift is in good agreement with the experiments. These results highlight the ability of KPFM to directly measure the electronic band structure in individual QDs of metal chalcogenide composites. This feature regulates charge dynamics in composite systems, thereby affecting device performance. This work provides valuable insights for applications in several fields, in which charge injection plays a major role. Abstract : The electrical properties of individual quantum dots (QDs) with different size and composition are studied with Kelvin Probe Force Microscopy (KPFM) . The KPFM is able to follow the variation of the Fermi level inside a single QD and to distinguish the different materials from the electronic point of view, without being influenced by the morphology of the sample.